Biomarkers for length of hospital stay, changes in muscle mass, strength and physical function in older medical patients: protocol for the Copenhagen PROTECT study—a prospective cohort study. Issue 12 (29th December 2020) - Kamper, Rikke S; Schultz, Martin; Hansen, Sofie K; Andersen, Helle; Ekmann, Anette; Nygaard, Hanne; Helland, Fredrik; Wejse, Miriam R; Rahbek, Camilla B; Noerst, Tim; Pressel, Eckart; Nielsen, Finn Erland; et al.
Abstract : Introduction: Sarcopenia is generally used to describe the age-related loss of muscle mass and strength believed to play a major role in the pathogenesis of physical frailty and functional impairment that may occur with old age. The knowledge surrounding the prevalence and determinants of sarcopenia in older medical patients is scarce, and it is unknown whether specific biomarkers can predict physical deconditioning during hospitalisation. We hypothesise that a combination of clinical, functional and circulating biomarkers can serve as a risk stratification tool and can (i) identify older acutely ill medical patients at risk of prolonged hospital stays and (ii) predict changes in muscle mass, muscle strength and function during hospitalisation. Method and analysis: The Copenhagen PROTECT study is a prospective cohort study consisting of acutely ill older medical patients admitted to the acute medical ward at Copenhagen University Hospital, Bispebjerg and Frederiksberg, Denmark. Assessments are performed within 24 hours of admission and include blood samples, body composition, muscle strength, physical function and questionnaires. A subgroup of patients transferred to the Geriatric Department are included in a smaller geriatric cohort and have additional assessments at discharge to evaluate the relative change in circulating biomarker concentrations, body composition, muscle strength and physical function during hospitalisation. Enrolment commenced 4 November 2019, and proceeds until August 2021. Ethics and dissemination: The study protocol has been approved by the local ethics committee of Copenhagen and Frederiksberg (H-19039214) and the Danish Data Protection Agency (P-2019-239) and all experimental procedures were performed in accordance with the Declaration of Helsinki. Findings from the project, regardless of the outcome, will be published in relevant peer-reviewed scientific journals in online (www.clinicaltrials.gov ). Trial registration number: NCT04151108